Effects of Financial Literacy and Self-Efficacy On Risky Credit Behavior of Gen-Z - Amanda Fortuna Arum Sekarlaras; Hermanto Siregar; Nur Hasanah (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The rise of digital technology has driven the growth of financial services like Paylater, enabling instant purchases with deferred payments. This has shifted financial habits, especially among Generation Z, who are more vulnerable to risky credit behavior. Therefore, understanding factors such as financial literacy and financial self-efficacy is essential to encourage responsible credit use.Purpose: The research focuses on analyzing the influence of financial literacy and financial self-efficacy on risky credit behavior among Generation Z in Indonesia. Design/methodology/approach: The study employs a quantitative research approach, utilizing a survey method to collect primary data from 141 Generation Z respondents in Indonesia who use online consumer credit services. The questionnaire assesses financial literacy, financial self-efficacy, and risky credit behavior. The collected data is analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate the relationships between financial literacy, financial self-efficacy, and risky credit behavior. Findings/Results: The study reveals that financial literacy significantly affects risky credit behavior. Furthermore, financial self-efficacy serves as a mediating variable, strengthening the influence of financial literacy on responsible credit management. Specifically, the results indicate that higher financial literacy leads to improved financial self-efficacy, and increased financial literacy reduces risky credit behavior. Financial self-efficacy directly decreases risky credit behavior, and financial self-efficacy successfully moderates the relationship between financial literacy and risky credit behavior, reinforcing responsible credit decisions. These findings highlight the importance of both financial knowledge and confidence in reducing credit risks among Generation Z consumers.Conclusion: This study confirms that financial literacy and financial self-efficacy play critical roles in shaping the credit behavior of Generation Z. Financial literacy equips individuals with the necessary knowledge to manage their finances effectively, while financial self-efficacy enhances their confidence in making informed financial decisions.Originality/value (State of the art): This research contributes to the growing body of knowledge on financial behavior by examining the interplay between financial literacy, financial self-efficacy, and risky credit behavior within the context of Generation Z's engagement with online consumer credit. Unlike previous studies that primarily focus on financial literacy alone, this study highlights the mediating role of financial self-efficacy, providing a more comprehensive understanding of how financial knowledge translates into behavior. The findings offer valuable insights for financial service providers, educators, and policymakers in designing interventions aimed at fostering financial responsibility among young consumers. Keywords: financial literacy, self-efficacy, risky credit behavior, online consumer credit, generation z